Respon Produksi dan Kualitas Benih Padi IPB 3S dan IPB 9G terhadap Aplikasi Boron pada Kondisi Lahan Kering - Ningsih, Riski Meliya; Lesta, Lesta (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Rice plants typically grow in paddy fields, but they can also be cultivated in dryland areas, known as upland rice. This study aims to examine the effect of applying the micronutrient boron on the growth and morphological characteristics of two rice varieties, IPB 3S and IPB 9G, conducted at the Leuwikopo experimental field of IPB using the legowo planting system. The treatments consisted of four combinations: no boron application on IPB 9G and IPB 3S varieties, and boron application on both varieties. Boron was applied at a concentration of 20 ppm through foliar spraying on the lower leaf surface three times during the growing period. Observations were made on plant characteristics, including leaf shape and position, plant height, number of tillers, flowering age, panicle exertion, and grain characteristics. Based on the results, it can be concluded that rice grain filling is influenced by pollen production and viability, which can increase the percentage of filled seeds and seed production. However, the production results in this study could not be analyzed due to bird pest attacks, which resulted in the absence of harvest data. Therefore, further research is recommended with more optimal plant protection to accurately obtain seed production data.